A systematic review of the effects of non-conscious regulatory processes in physical activity. Issue 4 (1st October 2016) - Rebar, Amanda L.; Dimmock, James A.; Jackson, Ben; Rhodes, Ryan E.; Kates, Andrew; Starling, Jade; Vandelanotte, Corneel
ABSTRACT: Physical activity theories have almost exclusively focused on conscious regulatory processes such as plans, beliefs, and expected value. The aim of this review was to aggregate the burgeoning evidence showing that physical activity is also partially determined by non-conscious processes (e.g., habits, automatic associations, priming effects). A systematic search was conducted and study characteristics, design, measures, effect size of the principle summary measures, and main conclusions of 52 studies were extracted by two independent coders. The findings support that habitual regulatory processes measured via self-report are directly associated with physical activity beyond conscious processes, and that there is likely interdependency between habit strength and intentions. Response latency measures of automatic associations with physical activity were widely disparate, precluding conclusions about specific effects. A small body of evidence demonstrated a variety of priming effects on physical activity. Overall, it is evident that physical activity is partially regulated by non-conscious processes, but there remain many unanswered questions for this area of research. Future research should refine the conceptualisation and measurement of non-conscious regulatory processes and determine how to harness them to promote physical activity.